CORELATION BETWEEN THE PROFESSIONAL COMPETENCE OF TEACHER GUIDANCE AND COUNSELING WITH PERFORMANCE GUIDANCE COUNSELING SERVICE AT SMA NEGERI IN METRO CITY - Atieka, Nurul; Kurniawati, Rina (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2015)
Abstract: Many of the problems related to the implementation of guidance and counseling services. Variable allegedly linked to the issue of counseling services is the professional competence of teachers BK. This study aims to determine the relationship between the professional competence of teachers guidance and counseling to the implementation of guidance and counseling services in SMA as the city Metro. Correlational research approach. The population in this study are all guidance and counseling teacher in SMA as the city Metro and there are 17 teachers guidance and counseling. the total sample. The instrument used was a questionnaire. Data analysis techniques use Product Moment formula. With the results obtained with the 0.57 significance level of 5% = 0.514. The conclusion of this study were: 1) the professional competence of teachers guidance and counseling are in the high category, 2) the implementation of guidance and counseling services are in high category, 3) there is a relationship between the professional competence of teachers guidance and counseling to the implementation of guidance and counseling services.Keyword: professional competence, Guidance and Counseling Services.